Strategies to Address Bullying in Schools: Building a Positive School Culture Amidst Social Challenges in the Digital Age - Epi Supiadi (PT. Anagata Sembagi Education, 2025)
Bullying in schools is a serious problem that impacts students' psychological, social and academic well-being. In the digital age, the phenomenon has become more complex with the emergence of cyber-bullying that can occur outside the school environment but still affects students' social dynamics. Lack of awareness, regulation and effective prevention strategies are challenges in creating a safe and inclusive learning environment. Therefore, a systematic approach is needed to address bullying and build a positive school culture to support students' optimal development. This study aims to identify the forms of bullying that occur in schools, evaluate the strategies that have been implemented in preventing and handling bullying, and analyze the supporting and inhibiting factors in building a positive school culture. This study used a qualitative approach with interview and observation methods. The results show that although some schools have implemented anti-bullying policies, challenges are still found in its implementation, especially in dealing with cyber bullying that is difficult to control. More effective intervention programs involve educational approaches, such as social skills training for students, strengthening the role of teachers and counselors in mentoring students, and active involvement of parents in bullying prevention. The implications of this study emphasize the importance of strengthening anti-bullying policies that are more adaptive to technological developments, increasing the competence of educators in handling bullying cases, and collaboration between schools, parents and communities in creating a safer, more inclusive school environment that supports holistic student development